When to start antiretroviral treatment? A history and analysis of a scientific controversy - Nathan Geffen; Marcus O. Low (AOSIS, 2017)
Background: Since 1987 HIV scientists and activists have debated the optimal point to start antiretroviral treatment. Positions have varied between treating people with HIV as soon as they are diagnosed, based on biological, modelling and observational evidence, versus delaying treatment until points in disease progression at which clinical trial evidence has shown unequivocally that treatment is beneficial. Objectives: Examining the conduct and resolution of this debate may provide insight into how science works in practice. It also documents an important part of the history of the HIV epidemic. Method: We describe clinical trials, observational studies, models and various documents that have advanced the debate from 1987 to 2015. Results and conclusion: Evidence accumulated over the past decade, especially from randomised controlled clinical trials, has shown that immediate treatment both reduces the mortality and the risk of HIV transmission; it benefits both public health and the individual patient. By mid-2015, the debate was resolved in favour of immediate treatment.